Hepatotoxicity of tocilizumab and anakinra in rheumatoid arthritis: management decisions - Mahamid M; Mader R; Safadi R (Dove Medical Press, 2011)
Mahmud Mahamid1,3, Reuven Mader4, Rifaat Safadi1,2 1Liver Unit, Holy Family Hospital, Nazareth, Israel; 2Hadassah Medical Center, Jerusalem, Israel; 3Shaare Zedek Medical Center, Jerusalem, Israel; 4Rheumatology Unit, Ha’emek Medical Center, Afula, Israel Background: Elevation of liver enzymes in rheumatoid arthritis patients treated with tocilizumab (Actemra®) or anakinra (Kineret®) is a well-documented phenomenon. However, characterization of liver histology has not been defined in most cases. Similarly, the factors involved in decisions regarding discontinuation of treatment and outcome have not been discussed in the literature to any significant extent. Cases: Two women with rheumatoid arthritis refractory to standard therapies are reported here. One was treated with tocilizumab and the other with anakinra, and both developed toxic liver effects. Liver biopsy in both cases showed focal necrosis of hepatocytes – a hallmark of drug toxicity – with steatosis and early fibrosis. Inflammatory infiltrates were prominent in the patient treated with anakinra but not in the tocilizumab-treated patient. However, FibroTest (Assistance publique – Hôpitaux de Paris, Paris, France) in the latter patient showed an inflammatory activity of A2 and was staged as F2, and the histology also showed hemorrhagic areas. Although both patients were overweight and both had been exposed to steroids, the steatosis and steatohepatitis were considered to be related to drug hepatotoxicity. Other possible etiologies for liver injury were excluded. Discontinuation of anakinra led to rapid normalization of liver enzymes. The patient receiving tocilizumab developed hepatosplenomegaly but had normal liver enzymes. In spite of the hepatosplenomegaly, the tocilizumab treatment was continued since the patient had not responded to other drugs. There was a good response to the tocilizumab treatment and the liver biopsy showed only insignificant, reversible liver injury. At follow-up at 6-months the patient remains stable. Conclusion: As cases showing tocilizumab or anakinra liver toxicity are appearing more frequently to the authors, a full assessment for liver injury is recommended in patients given those drugs, with careful consideration of the decision to continue or discontinue treatment. Further studies with long-term follow-up analysis are mandatory to guide appropriate management strategies. Keywords: anakinra, interleukin receptors, liver injury, rheumatoid arthritis, tocilizumab